Cardiovascular event rates and mortality according to achieved systolic and diastolic blood pressure in patients with stable coronary artery disease: an international cohort study. Issue 10056 (29th October 2016) - Vidal-Petiot, Emmanuelle; Ford, Ian; Greenlaw, Nicola; Ferrari, Roberto; Fox, Kim M; Tardif, Jean-Claude; Tendera, Michal; Tavazzi, Luigi; Bhatt, Deepak L; Steg, Philippe Gabriel; ,
Summary: Background: The optimum blood pressure target in hypertension remains debated, especially in coronary artery disease, given concerns for reduced myocardial perfusion if diastolic blood pressure is too low. We aimed to study the association between achieved blood pressure and cardiovascular outcomes in patients with coronary artery disease and hypertension. Methods: We analysed data from 22 672 patients with stable coronary artery disease enrolled (from Nov 26, 2009, to June 30, 2010) in the CLARIFY registry (including patients from 45 countries) and treated for hypertension. Systolic and diastolic blood pressures before each event were averaged and categorised into 10 mm Hg increments. The primary outcome was the composite of cardiovascular death, myocardial infarction, or stroke. Hazard ratios (HRs) were estimated with multivariable adjusted Cox proportional hazards models, using the 120–129 mm Hg systolic blood pressure and 70–79 mm Hg diastolic blood pressure subgroups as reference. Findings: After a median follow-up of 5·0 years, increased systolic blood pressure of 140 mm Hg or more and diastolic blood pressure of 80 mm Hg or more were each associated with increased risk of cardiovascular events. Systolic blood pressure of less than 120 mm Hg was also associated with increased risk for the primary outcome (adjusted HR 1·56, 95% CI 1·36–1·81). Likewise, diastolic blood pressure of less than 70 mm Hg was associated with an increase in the primary outcome (adjusted HR 1·41 [1·24–1·61] for diastolic blood pressure of 60–69 mm Hg and 2·01 [1·50–2·70] for diastolic blood pressure of less than 60 mm Hg). Interpretation: In patients with hypertension and coronary artery disease from routine clinical practice, systolic blood pressure of less than 120 mm Hg and diastolic blood pressure of less than 70 mm Hg were each associated with adverse cardiovascular outcomes, including mortality, supporting the existence of a J-curve phenomenon. This finding suggests that caution should be taken in the use of blood pressure-lowering treatment in patients with coronary artery disease. Funding: Servier.